LEED-IV analyses of tellurium adsorbate structures on iridium and gold surfaces - Hammer, Lutz; Schewski, Alexandra; Wegerich, Alexander; Kißlinger, Tilman; Schneider, M. Alexander (Surface Science, 2024)
The determination of the configuration of atomic adsorbates on clean metal surfaces has been a key issue in surface science 60 years ago and still is today. We demonstrate that despite the prevalence of combined scanning tunneling microscopy and density functional theory studies of adsorbate systems the pitfalls are plentiful calling for accurate, reliable structure analyses that can be delivered by diffraction methods. We analyze and compare the ordered phases of Te on Ir(111), Ir(100), and Au(100) demonstrating the accuracy, the in-depth information and physical insight that can nowadays be obtained by quantitative low-energy electron diffraction structural analyses.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Adsorbate; LEED-IV; Structural analysis; Tellurium

Tellurization of Pd(111) revisited: Formation of a TePd2 surface alloy but no PdTe2 monolayer - Engel, Eric; Wegerich, Alexander; Raabgrund, Andreas; Schneider, M. Alexander (Surface Science, 2024)
In a recent publication [2D Materials, 8, 045033 (2021)], it was reported that the growth of a monolayer PdTe2 in ultra-high vacuum could be achieved by deposition of tellurium on a palladium (111) crystal surface and subsequent thermal annealing. By means of low-energy electron diffraction intensity (LEED-IV) structural analysis, we show that the obtained 3×3R30° superstructure is in fact a TePd2 surface alloy. Attempts to produce a PdTe2 layer in ultra-high vacuum by increasing the Te content on the surface were not successful.
CRIS-Team Scopus Importer:2024-06-14
Keywords: LEED-IV; Palladium; Structural analysis; Surface alloy; Tellurium; Transition metal dichalcogenide